Victims’ versus ‘offenders’ in British political discourse: the construction of a false dichotomy - Drake, Deborah H.; Henley, Andrew (Wiley, 2014)
This article evaluates the contemporary discursive status of victims and people convicted of criminal offences. The rhetoric used by British politicians to convey the meaning of ‘rights’ is explored within media output, parliamentary speech-making and other forms of political discourse. Our analysis details how victims’ rights are sometimes advocated for at the expense of ‘offenders’’ rights in public discourse. Examination of parliamentary debates illustrates that differentiating between ‘victims’ and ‘offenders’ elides consideration of more meaningful support for victims, worsens opportunities for the reintegration of ex-prisoners and constructs a false dichotomy between citizens who do not fall into mutually-exclusive categories.